2008
DOI: 10.1007/s11258-008-9518-7
|View full text |Cite
|
Sign up to set email alerts
|

Consistent pattern of habitat and species selection by post-dispersal seed predators in a Mediterranean mosaic landscape

Abstract: There is still little information on effects of habitat degradation on post-dispersal seed predation at the landscape scale. The aim of this study was to determine the influence of habitat degradation and seed species on the variability of post-dispersal seed-predation rate. Experimental seed removal was investigated in six Mediterranean woody plant species, four trees (Pinus sylvestris, Quercus ilex, Acer opalus ssp. granatense, and Sorbus aria) and two shrubs (Berberis vulgaris and Crataegus monogyna), in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 60 publications
3
29
0
Order By: Relevance
“…Similarly at Escobarejos, the density of dispersed seeds in 2006 suggests a smaller fruit production than in 2007, which might explain the absence of mammal scats for this year. Despite their potential to disperse the seeds over long distances (Jordano et al, 2007;Matías et al, 2009), their role as efficient seed dispersers remain unclear. Indeed, Peredo et al (2013) found that they deposited a large fraction of the seeds into unsuitable microhabitats for germination and seedling establisment, such as latrines in the case of badgers, a microsite where seeds are probably faced to overcrowding and recurrent disturbance (but see Escribano-Avila et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly at Escobarejos, the density of dispersed seeds in 2006 suggests a smaller fruit production than in 2007, which might explain the absence of mammal scats for this year. Despite their potential to disperse the seeds over long distances (Jordano et al, 2007;Matías et al, 2009), their role as efficient seed dispersers remain unclear. Indeed, Peredo et al (2013) found that they deposited a large fraction of the seeds into unsuitable microhabitats for germination and seedling establisment, such as latrines in the case of badgers, a microsite where seeds are probably faced to overcrowding and recurrent disturbance (but see Escribano-Avila et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the great spotted woodpeckers Dendrocopos major L. is one of the main predators of seeds in closed cones of P. sylvestris in central and eastern Europe (Myczko & Benkman, 2011), while the crossbill (Loxia curvirostra L.) feeds on ripening seeds in southern Spain (Castro et al, 1999). Predation pressure shows an interannual variability that may be related to temporal variation in cone production (Matias et al, 2009). Although pre-and post-dispersal predation can reduce the seed pool of P. sylvestris to almost 50% (Worthy et al, 2006) or even over 90% in relict P. sylvestris forests in southern Spain (Castro et al, 1999), it is unlikely to be a serious problem for the regeneration of the species in Sierra de Guadarrama, except in the lower limit, where seed production is much more scarce.…”
Section: Pre and Post-dispersal Seed Predationmentioning
confidence: 99%
“…Seed dispersal by carnivorous mammals only accomplishes a low proportion of animal-generated seed rain in these shrublands (Matı´as et al 2008). The seeds of the target shrub species suffer predation after dispersal by A. sylvaticus (Garcı´a-Castaño et al 2006, Matı´as et al 2009). …”
Section: Mediterranean Shrublandmentioning
confidence: 99%
“…2). We assumed that the detection of seeds in open quadrats provides a reliable measure of the initial spatial template of seed availability for post-dispersal seed predators, notwithstanding some early seed removal by rodents, because of the following reasons: (1) seeds found in the remains of birds droppings are very conspicuous and easily distinguishable from the soil background, even when washed by rain; (2) seed removal by diurnal animals was never observed, and removal by nocturnal rodents is low during most of the dispersal season as predation frequency peaks late in winter (Garcı´a et al 2005a, Matı´as et al 2009); (3) any seed showing signs of predation (open husk or teeth marks) found in the quadrats was considered a dispersed seed; and (4) a previous work in the same Cantabrian site demonstrated the suitability of seed monitoring in quadrats, by comparing seed deposition in quadrats open to predators with seed deposition in paired seed traps that excluded predators (Garcı´a et al 2005b). …”
Section: Sampling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation